Infrastructure and Growth (The Pakistan Development Review, 2011)
Physical Infrastructure stocks in Pakistan since the last two decades have been growing at a very low pace which resulted in increasing unemployment and very low economic growth in the last four years. The paper analyses the link between infrastructure, productivity and growth in Pakistan by applying two distinct methodologies—growth accounting and growth regressions. We find out that infrastructure stock has significantly positive impact on productivity and economic growth. At the individual level, electricity generation, agricultural water availability and telecommunications impact the economic growth positively and significantly, while, roads development have no impact. This is an indication of over investment in roads, especially highways. Based on model findings, we recommended that Pakistan will have to increase the allocation of PSDP to above 1.5 percent of the GDP if the problem of shortage of electricity is to be addressed on a priority basis so as to raise the growth rate of the economy.